Seismic pullout behavior of cast-in-place anchor bolts embedded in plain concrete: Damage plasticity based analysis. (December 2021) - Shafei, Erfan; Tariverdilo, Saeed
Abstract: The seismic pullout strength of the cast-in-place anchor bolts embedded in the plain concrete is a function of the accumulated tensile damage during the load reversals. The present study deals with the seismic tension analysis of the cast-in-place anchor bolts considering the resultant stiffness and strength degradation phenomena. In this way, a nonlinear fracture-based damage plasticity model is developed and implemented in the Abaqus code. Primarily, the validity and accuracy of the developed constitutive model are assessed based on the existing pullout tests. Then, the developed framework is utilized to assess the seismic pullout response of the anchor bolts with a low embedded depth-to-diameter ratio ( h e d b ⩽ 10 ) . Assumed parametric study space contains several plain slabs with various anchor diameters, embedded depths, and compressive concrete strengths. Based on the observations, the seismic load results in significant degradation of stiffness (damage) and pullout strength. The seismic-induced damage is increased when the compressive concrete strength and the embedded anchor depth are increased. However, the slender anchors undergo lower damage than the stubby ones. The size effect phenomenon in the concrete material leads to distinct behavior of the cast-in-place anchor bolts with various embedded depth-to-diameter ratios. Considering the crack patterns of the modeled slabs, the degraded stiffness state at the end of the seismic loading step increases the inclination angle of the pullout cracks during the monotonic loading step. The inclination angle of the cracks is detected to be a function of the embedded depth-to-diameter ratio.